2022
DOI: 10.3389/fnins.2022.901337
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting two-point discrimination in Argus II patients

Abstract: Two of the main obstacles to the development of epiretinal prosthesis technology are electrodes that require current amplitudes above safety limits to reliably elicit percepts, and a failure to consistently elicit pattern vision. Here, we explored the causes of high current amplitude thresholds and poor spatial resolution within the Argus II epiretinal implant. We measured current amplitude thresholds and two-point discrimination (the ability to determine whether one or two electrodes had been stimulated) in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…While it is not surprising that two electrodes separated by a large retinal distance might produce two distinct phosphenes (Yücel et al 2022), here we were able to split retinal distance into two (nearly orthogonal) components: between-axon distance, which measures how far the electric current must spread away from an axon bundle until it reaches another electrode, and along-axon distance, which measures how far the electric current must spread along an axon bundle until it reaches another electrode. We found that models relying on between-axon distance consistently outperformed models relying on along-axon distance when predicting the number of perceived phosphenes (table 8).…”
Section: The Number Of Perceived Phosphenes Depends On the Axonal Dis...mentioning
confidence: 88%
See 3 more Smart Citations
“…While it is not surprising that two electrodes separated by a large retinal distance might produce two distinct phosphenes (Yücel et al 2022), here we were able to split retinal distance into two (nearly orthogonal) components: between-axon distance, which measures how far the electric current must spread away from an axon bundle until it reaches another electrode, and along-axon distance, which measures how far the electric current must spread along an axon bundle until it reaches another electrode. We found that models relying on between-axon distance consistently outperformed models relying on along-axon distance when predicting the number of perceived phosphenes (table 8).…”
Section: The Number Of Perceived Phosphenes Depends On the Axonal Dis...mentioning
confidence: 88%
“…Across all participants, shape descriptors tended to sum linearly, with the β values suggesting that phosphenes elicited by paired-electrode stimulation appeared larger than the average of their single-electrode counterparts, but smaller than their sum. Yücel et al (2022) previously demonstrated that the probability of perceiving two distinct phosphenes increases with inter-electrode distance. However, the axon map model (Beyeler et al 2019b) makes a more nuanced prediction: participants should be more likely to see two distinct phosphenes as the distance between two nerve fiber bundles increases ('betweenaxon' distance; as opposed to distance on the retinal surface; see Methods).…”
Section: Factors Affecting Phosphene Shape During Paired-electrode St...mentioning
confidence: 98%
See 2 more Smart Citations
“…between-axon distance (green lines in Fig. 3): the shortest distance between the center of the more nasal electrode to the closest axon of the more temporal electrode;
Figure 3: Axonal distances (adapted from Yücel et al, 2022). A) The between-axon distance (green line) and the along-axon distance (blue curve) when two electrodes are on the same side of the raphe, B) and when two electrodes are on different sides.
…”
Section: Methodsmentioning
confidence: 99%